The abominable snowman. - Tucker, Forrest, 1919-1986; Cushing, Peter, 1913-1994; Connell, Maureen; Wattis, Richard; Brown, Robert; Guest, Val (Hammer collection.)
Botanist Dr. John Rollason (Peter Cushing) joins the exploration team of crass into the Himalayas to search for the legendary Yeti. While setting up camp, the group is attacked by a large beast and than shot by Ed Shelley (Robert Brown) and later stored in a cave to attract live specimen.